Colubrina javanica Miq. (Rhamnaceae) A new angiosperm record for Bangladesh (Bangladesh Journal of Plant Taxonomy, 2014)
Not availableDOI: http://dx.doi.org/10.3329/bjpt.v21i2.21362Bangladesh J. Plant Taxon. 21(2): 199-202, 2014 (December)